Central African Economic and Monetary Community (CEMAC) : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper looks at some Central African Economic and Monetary Community (CEMAC) specific regional dimensions of a possible strategy to enhance governance, which would support specific reforms in this area at the country level. The paper describes the specific dimensions of governance covered in the note. The paper also analyzes governance and corruption in the areas of public financial management, anti-money laundering, and the link between the oil sector and public resources. The CEMAC regional institutions will have to play a central role to lead progress in these areas, and support member countries' own efforts. Due to such actions result in giving a coherent framework to actions conducted at the country level, the synergic dimension can spur a virtuous circle, key to earn the benefit of an economic and monetary union. The success of the regional strategy that CEMAC member countries and regional institutions are implementing to exit the severe crisis they are facing depends critically on creating the conditions for laying the ground for a diversified economy, within a well-functioning regional market and an environment that provides opportunities for all and where public resources are geared to most productive use.